Citizens on Patrol: Understanding Public Whistleblowing against Government Corruption. (24th March 2018) - Su, Xuhong; Ni, Xing
Abstract: Despite the importance of public whistleblowing, there has been little systematic inquiry into the topic. Combining objective and self-reported data, this study attempts to sort out the dynamics of public whistleblowing against government corruption, particularly distinguishing the antecedents of whistleblowing intention from those of actual whistleblowing acts and exploring anonymity decisions. A middle-range theory is proposed that highlights individual, situational, and institutional forces as they pertain to public whistleblowing. The results portray public whistleblowing to be driven by a complex array of competing motives and dynamics. The antecedents of whistleblowing intention are different in non-trivial ways than those of actual acts, with intention being prosocial motives and actual acts akin to voluntary provision of public goods. Institutional anticorruption yields both complementary and substitute effects on public whistleblowing. The study concludes with discussing the implications for further theory development and practical guidance.